2002
DOI: 10.1094/phyto.2002.92.9.997
|View full text |Cite
|
Sign up to set email alerts
|

Internal Transcribed Spacer Regions 1 and 2 and Random Amplified Polymorphic DNA Analysis ofDidymella bryoniaeand RelatedPhomaSpecies Isolated from Cucurbits

Abstract: Didymella bryoniae (anamorph Phoma cucurbitacearum) is the causal agent of gummy stem blight, although other Phoma species are often isolated from cucurbit plants exhibiting symptoms of the disease. The molecular and phylogenetic relationships between D. bryoniae and these Phoma species are unknown. Isolates of D. bryoniae and Phoma obtained from cucurbits grown at various geographical locations in the United States were subjected to random amplified polymorphic DNA (RAPD) analysis and internal transcribed spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 21 publications
4
38
0
1
Order By: Relevance
“…ITS sequence data are typically used to define organisms at the genus level and resolve relationships between closely related species (Gardes et al, 1991;Bakkeren et al, 2000;Somai et al, 2002;Stoll et al, 2003). This was observed following comparison of sequence data from S. scitamineum isolates used in this study with those of published sequences for other members of Sporisorium and Ustilago (Table 3 and Figures 4 to 6).…”
Section: Discussionmentioning
confidence: 95%
“…ITS sequence data are typically used to define organisms at the genus level and resolve relationships between closely related species (Gardes et al, 1991;Bakkeren et al, 2000;Somai et al, 2002;Stoll et al, 2003). This was observed following comparison of sequence data from S. scitamineum isolates used in this study with those of published sequences for other members of Sporisorium and Ustilago (Table 3 and Figures 4 to 6).…”
Section: Discussionmentioning
confidence: 95%
“…An earlier study showed the usefulness of RAPD analysis in detecting 4 Dendrogram based on Jaccard's Similarity Coeffi cient generated by UPGMA analysis of four Phoma species using fi ve RAPD markers signifi cant polymorphisms between Didymella. bryoniae and Phoma species [36][37][38]. The present study expands the previous study by using RAPD analysis on a pigment producing collection of four isolates to determine their phylogenetic relationships.…”
Section: Discussionmentioning
confidence: 75%
“…Vários trabalhos foram conduzidos utilizando seqüenciamento ou análises de marcas RFLP da região ITS (Wang et al, 1998;Miller et al, 1999;Dunkle & Levy, 2000;Nielsen et al, 2001;Somai et al, 2002), demonstrando diferenças genéticas importantes em genótipos morfologicamente indistintos.…”
Section: Métodos Moleculares Para Detecção De Diversidade Genéticaunclassified